PENGARUH AKTIVITAS MANUSIA TERHADAP DEGRADASI EKOSISTEM PANTAI DI PULAU TAGALAYA, KABUPATEN HALMAHERA UTARA - Bayau, Edom; Suhry, Hendro C.; Senen, Misda Alberto; Erbabley, Baltazar Z. (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Coastal ecosystems play a strategic role in maintaining environmental balance while supporting the socio-economic livelihoods of coastal communities. However, increasing human activities have become a major driver of ecosystem degradation. This study aims to analyze the forms of human activities, assess the condition of coastal ecosystems, and examine the influence of human activities on environmental degradation in Tagalaya Island, North Halmahera Regency. The research employed a mixed-methods approach, combining surveys, field observations, interviews, and questionnaires. Data were analyzed using descriptive and quantitative techniques, including scoring and simple regression analysis. The results indicate that human activities are categorized as high, particularly in the tourism and pollution sectors. Plastic waste dominates coastal pollution, accounting for 60% of total waste, while tourist visits increase significantly during weekends. The condition of coastal ecosystems shows moderate to high levels of degradation. Mangrove ecosystems have experienced 25% damage, coral reefs are in an unstable condition, and seagrass beds show early signs of environmental stress. In addition, coastal abrasion occurs at an average rate of approximately ±2 meters per year, indicating ongoing physical degradation of the shoreline. The analysis reveals a positive relationship between human activities and ecosystem degradation, with both variables scoring 11. This finding confirms that increasing human activities directly correlate with higher levels of environmental damage. Therefore, sustainable management strategies are essential to preserve the balance and resilience of coastal ecosystems.